Adapting Chekhov : the text and its mutations - Clayton, J. Douglas; Meerzon, Yana (Routledge advances in theatre and performance studies, 2013)
This book considers the hundred years of re-writes of Anton Chekhov's work, presenting a wide geographical landscape of Chekhovian influences in drama. The volume examines the elusive quality of Chekhov's dramatic universe as an intricate mechanism, an engine in which his enigmatic characters exist as the dramatic and psychological ciphers we have been de-coding for a century, and continue to do so. Examining the practice and the theory of dramatic adaptation both as intermedial transformation (from page to stage) and as intramedial mutation, from page to page, the book presents adaptation as.